Pengaruh Brand Association, Nutrition Label, dan Trust Terhadap Perilaku Pasca Pembelian Produk Cimory Yogurt - Okky Pramudya Wardana; Mintarti Indartini; Ahadiati Rohmatiah (Universitas Merdeka Madiun, 2026)
This study aims to analyze the partial and simultaneous influence of brand association, nutrition labels, and trust on the post-purchase behavior of Cimory Yogurt products in the Ngawi District. This type of research is quantitative, with primary data sources covering a sample of 384 respondents. Data was collected through questionnaires and analyzed using multiple linear regression, with data analysis techniques including the t-test, F-test, and the coefficient of determination (R²). The results of the study indicate that partially, brand association, nutrition labels, and trust each have a positive and significant influence on the post-purchase behavior of Cimory Yogurt products in the Ngawi District. Simultaneously, these three variables are also proven to have a significant influence on the post-purchase behavior of Cimory Yogurt products in Ngawi District. These findings indicate that positive brand associations, clear nutritional information, and consumer trust are key factors driving loyalty and repeat purchases.